The relationship between tooth loss and cognitive function among elderly: a cross-sectional study - Mustofa, Winda Fauzul; Indriana, Tecky; Joelijanto, Rudy (Padjadjaran Journal of Dentistry, 2025)
Introduction: Tooth loss refers to the condition in which teeth are dislodged  from their sockets. In elderly individuals, tooth loss can lead to reduced chewing ability, which may contribute to a higher likelihood of cognitive function. The purpose of this study was to analyze the relationship between tooth loss and cognitive function among the elderly. Methods: The study employed an analytical observational method with a cross-sectional design. Participants were recruited using a purposive total sampling technique. Subjects were selected based on specific inclusion and exclusion criteria, resulting in a final sample size of 48 participants. All participants provided informed consent, and data were collected using the Mini-Mental State Examination (MMSE) questionnaire. The data were tabulated and analyzed descriptively, followed by a Spearman correlation test with a significance threshold set at 0.000 (p-value <0.05). Results: The correlation coefficient was found to be 0.487, indicating a moderate positive relationship between tooth loss and cognitive function among elderly. Conclusion: There is a moderate positive relationship between tooth loss and cognitive function among elderly.